Culture, identity and conflict in Asia and Southeast Asia - Croissant, Aurel; Trinn, Christoph (Asien, 2009)
This essay analyzes cultural conflicts in Asia with particular emphasize on Southeast Asia. Cultural conflict is defined as those domestic, inter-state or transnational political conflicts in which the actors involved focus on issues relating to religion, language and/or historicity. The statistical analysis and the assessment of individual cases in this paper substantiate number of conclusions. First, by global comparison, Asia is region particularly prone to conflicts. Second, domestic conflicts about identity and especially historicitary conflicts, predominate in the region. Third, the landscape of conflict in Asia is characterized by pronounced domestic conflicts of low intensities over identity. Fourth, conflicts in Asia are shaped by the dominance of "ethnic" actors. In recent decades the relevance of left-wing actors has declined, whereas the importance of religiously defined actors has increased. Fifth, compared with the rest of Asia, Southeast Asia is subject to disproportionally large number of cultural conflicts. At the same time, however, it is important to note that in Southeast Asia there is no trend of further culturalization of conflicts in recent years. Rather, the identity conflicts in Southeast Asia seem to be very profound and as such are frequently quite resistant to de-escalation strategies. However, cultural conflicts in the region are almost exclusively of an internal nature and do not extend to inter-state relations.